Ilmu Pengetahuan Dan Agama Dalam Filsafat - sigit purnomo; Muntaha . (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The background of this research stems from the question of whether science, religion, and philosophy are related and interconnected. Therefore, I conducted this research with the aim of understanding the relationship between science, religion, and philosophy and how we should approach philosophy. This research used a qualitative method based on literature review, which involved searching for and reading books and scholarly works on philosophy, science, and religion. The results showed that science, religion, and philosophy are closely related and interconnected. Philosophy is the source of knowledge, which then, through science, has created the advanced technology we have today. Religion is a guide for human life, enabling us to live in an orderly and orderly manner, following the guidance of Allah Subhanahu wa Ta'ala, rationally and scientifically, thus avoiding the shackles of myth and superstition. However, it is important to be careful when studying philosophy, not to overdo it and not to overdo it. Nor should we reject philosophy, thus preventing rational thinking, which ultimately leads to superstitious beliefs and myths, which would regress us backward to civilization before ancient Greece.